2004
DOI: 10.1354/vp.41-3-275
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Myogenic Regulating Factors, Myogenin and MyoD, in Two Canine Botryoid Rhabdomyosarcomas

Abstract: Myogenin and MyoD regulate the development of skeletal muscle, and their expressions are specific to the stages of myogenesis. Therefore, these myogenic regulatory proteins could be considered as sensitive and specific markers for rhabdomyosarcoma. In this report we investigated the immunohistochemical reactivities of myogenin and MyoD in two canine bladder botryoid rhabdomyosarcomas that were different in the degree of differentiation. MyoD was stained in the Ki-67 antigen-positive undifferentiated mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 5 publications
2
27
0
5
Order By: Relevance
“…However, there seems to be a trend of similarity with what has been reported in humans, regarding the fact that the majority of rMSs in dogs have occurred in tissues that normally do not contain striated-muscle cells, such as the pharynx, gingiva, urethra, trachea, larynx and the jawbone (Seibold, 1974;Sarnelli et al,1994;yanoff et al, 1996;Ginel et al, 2002;, Illanes, 2002;Kobayashi et al, 2004;Suzuki et al, 2006;Bae et al, 2007;Murakami et al, 2010). A few cases of canine rMSs have been reported to arise from striated muscles (Worley and Gorham, 1954;Gonin-Jmaa et al, 1996;Kim et al, 1996;Lascelles et al, 1998;Pérez et al, 1998;Cooper and Valentine, 2002;Machida et al, 2003;Brockus and Myers, 2004;Akkoc et al, 2006;Aupperle et al, 2007;Nakaichi et al, 2007;Chapman et al, 2008;yhee et al, 2008;yamate et al, 2011) and only some of them were further classified.…”
Section: Introductionmentioning
confidence: 63%
“…However, there seems to be a trend of similarity with what has been reported in humans, regarding the fact that the majority of rMSs in dogs have occurred in tissues that normally do not contain striated-muscle cells, such as the pharynx, gingiva, urethra, trachea, larynx and the jawbone (Seibold, 1974;Sarnelli et al,1994;yanoff et al, 1996;Ginel et al, 2002;, Illanes, 2002;Kobayashi et al, 2004;Suzuki et al, 2006;Bae et al, 2007;Murakami et al, 2010). A few cases of canine rMSs have been reported to arise from striated muscles (Worley and Gorham, 1954;Gonin-Jmaa et al, 1996;Kim et al, 1996;Lascelles et al, 1998;Pérez et al, 1998;Cooper and Valentine, 2002;Machida et al, 2003;Brockus and Myers, 2004;Akkoc et al, 2006;Aupperle et al, 2007;Nakaichi et al, 2007;Chapman et al, 2008;yhee et al, 2008;yamate et al, 2011) and only some of them were further classified.…”
Section: Introductionmentioning
confidence: 63%
“…Myogenin is considered as the most critical marker for human rhabdomyosarcoma (Dias et al 2000). In the veterinary literature, Kobayashi et al (2004) reported the expression of myogenin and MyoD in two canine botryoid rhabdomyosarcomas, and myogenin was found to be a useful marker for canine rhabdomyosarcoma. However, there has been no reported case of alveolar rhabdomyosarcoma confirmed using an anti-myogenin antibody in the veterinary literature.…”
Section: Discussionmentioning
confidence: 99%
“…Myogenin induces differentiation of myoblasts into the multinucleated myotube, which has abundant cytoplasm containing myofibrils. Myogenin is one of the myogenic transcriptional factors expressed in the early stage of muscle development and its expression differs depending on the stage of myogenesis (Kobayashi et al 2004). Myogenin is intensely expressed during the late stages of myoblast differentiation and during myotube formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During myogenesis, MyoD1 plays an essential role in differentiation of primitive mesenchymal cells into myoblasts, and subsequently, myogenin induces differentiation of the myoblasts into the myotubes. Because myogenin is expressed after MyoD1 in the development process of striated muscle cells, early myoblasts may have MyoD1 expression but lack myogenin expression [10,12,14]. It is also known that, after maturation, resting adult muscle cell do not express MyoD1 or myogenin [5].…”
mentioning
confidence: 99%